34 Case report of sertraline exacerbation of tics in tourette's with OCD. Issue 8 (20th July 2020) - Paramlall, Mark; Tyagi, Himanshu
Abstract : Introduction: Tourette Syndrome (TS) is a prototypical Neuropsychiatric neurodevelopmental disorder consisting of multiple motor tics and at least one vocal tic, usually preceding the motor tic, with onset prior to age 18 and of a duration of at least 1 year. 1 2 It is estimated that 50% of TS patients demonstrate OCD behaviours during their lifetime. 3 Selective Serotonin Reuptake Inhibitors (SSRI's) are approved for treatment of depression and for OCD. There are literature reports of the SSRIs, exacerbating or causing tics. However, in all the cases described, symptoms resolved on cessation of Sertraline. We present below a case report of a patient in which this was not the case. Case Report: Our patient was a 22-year-old man an unremarkable medical and psychiatric history except mild childhood tics, resolved in adulthood, was referred with a 3-year history of disabling tics (vocal and motor) of sudden onset after using Sertraline prescribed for depression. Three days post Sertraline he began singing his conversation, swearing and suffering from muscle twitches. His symptoms evolved to include: facial tics (masseter spasms, blinking, puffing of his cheek, expelling air through his lips, forehead wrinkling), complex thoracic and upper limb tics (violent head turnings with a hand grabbing motion, shrugging shoulders with violent right arm movements imitating a severe precordial thump, upper limb shaking with spasms and episodes of punching outwards and upper limb flexion with fingers curled as if he is holding an object such as a gun), Lower limb tics (hip gyration, kicking and occasional foot tapping) and vocal tics (simple and complex). Tics were associated with premonitory urge with increased anxiety and intensity on voluntary inhibition. Investigations were unremarkable and included an LP, blood tests with immunological profile, photo stimulation EEG and an MRI. Unsuccessful treatment modalities employed: CBT for twitches (24 sessions) and psychopharmacological interventions (Risperidone, Haloperidol and Quetiapine. Family history was significant for Sertraline intolerance. He was treated with Aripiprazole 2.5 mg for his diagnosis of Gilles la Tourette syndrome with comorbid OCD. Results: The subject responded well to Aripiprazole with reduced tic episodes. Conclusion: The above case is the only one in the literature to identify a family history of sertraline intolerance and requiring treatment with D2 modulator and a 5HT agonist for tic cessation after tic exacerbation post Sertraline treatment. References: Robertson MM, Eapen V. Cavanna AE, et.al. The international prevalence, epidemiology and clinical phenology of Tourette Syndrome: a cross cultural perspective. J Psychosom Res 2009; 67 (6): 475–83 American Psychiatric Association. Diagnostic and Statistical Manual of Mental Disorders. 5th Edition. Arlington (VA): American Psychiatric Association, 2013 Leckman JF, Pauls DL, Cohen DJ. Tic disorders. In: Bloom FE, Kupfer DJ. (eds). Psychopharmacology: The fourth Generation of Progress . New York: Raven Press, 1995, 1665–1674